2020
DOI: 10.1049/iet-rsn.2019.0601
|View full text |Cite
|
Sign up to set email alerts
|

300 GHz radar object recognition based on deep neural networks and transfer learning

Abstract: The copyright in this thesis is owned by the author. Any quotation from the thesis or use of any of the information contained in it must acknowledge this thesis as the source of the quotation or information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 130 publications
(282 reference statements)
0
10
0
Order By: Relevance
“…The Range-Doppler-Azimuth spectrums extracted from automotive radar sensors have been used frequently as 2D image inputs to various deep learning algorithms for different tasks, ranging from obstacle detection to segmentation, classification, and identification in autonomous driving systems [ 122 , 123 , 124 , 125 , 126 ]. The authors of [ 122 ] presented a method to recognize objects in Cartesian coordinates using a high-resolution 300-GHz scanning radar based on deep neural networks. They applied a fast Fourier transform (FFT) on each of the received signals to obtain the radar image.…”
Section: Detection and Classification Of Radar Signals Using Deep mentioning
confidence: 99%
“…The Range-Doppler-Azimuth spectrums extracted from automotive radar sensors have been used frequently as 2D image inputs to various deep learning algorithms for different tasks, ranging from obstacle detection to segmentation, classification, and identification in autonomous driving systems [ 122 , 123 , 124 , 125 , 126 ]. The authors of [ 122 ] presented a method to recognize objects in Cartesian coordinates using a high-resolution 300-GHz scanning radar based on deep neural networks. They applied a fast Fourier transform (FFT) on each of the received signals to obtain the radar image.…”
Section: Detection and Classification Of Radar Signals Using Deep mentioning
confidence: 99%
“…Yang et al [40] used deep transfer learning to identify military targets under small training conditions and got excellent recognition effect results. Sheeny et al [41] identified objects in 300 GHz radar images based on depth neural network and migration learning and then considered detection and classification in multiple object scenes. The deep neural network is based on a large data set, and the weight is obtained after multiple training.…”
Section: Deep Transfermentioning
confidence: 99%
“…Frequency-Modulated Continuous-Wave (FMCW) radar is receiving increased attention for exploitation in autonomous applications, including for problems related to SLAM [6][7][8][9] as well as scene understanding tasks such as object detection [10], and segmentation [11]. This increasing popularity is evident in several urban autonomy datasets with a radar focus [12,13].…”
Section: Navigation and Scene Understanding From Radarmentioning
confidence: 99%